The Diversity and Potential of Avitourism in Peat Swamp Ecosystem of Ayer Hitam Utara Forest Reserve, Johor - Ng, Wei Inn Valerience; Norazlimi, Nor Atiqah (Journal of Sustainable Natural Resources, 2022)
Avitourism is a responsible and tourism activity where birdwatchers perform bird-watching, which can be either a hobby or a dedicated practice. Bird-watching is an act of observing and identifying birds in their natural environment. It can be performed by using the naked eye, using binoculars or scope for visual enhancement, listening to bird songs, or using public cams. Ayer Hitam Utara Forest Reserve is a peat swamp forest, a type of tropical moist forest with a dense layer of acidic peat and serves as a habitat for a diverse range of species. This study aims to identify bird species present in Ayer Hitam Utara Forest Reserve and evaluate the potential of avitourism in Ayer Hitam Utara Forest Reserve. A questionnaire was passed to 51 respondents to collect their opinions on developing Ayer Hitam Utara Forest Reserve as an avitourism site. Point count method and mist-netting were performed to record bird species spotted during the sampling period. The sampling has recorded 33 species in total, where there are 2 Vulnerable, 3 Near-Threatened, and 1 Endangered species, and 20 out of 33 species are totally protected under Wildlife Conservation Act 2010. The respondents have given generally positive feedback and are interested in visiting Ayer Hitam Utara Forest Reserve. Avitourism can potentially benefit Ayer Hitam Utara Forest Reserve in economic, social, and environmental.Avitourism is a responsible and tourism activity where birdwatchers perform bird-watching, which can be either a hobby or a dedicated practice. Bird-watching is an act of observing and identifying birds in their natural environment. It can be performed by using the naked eye, using binoculars or scope for visual enhancement, listening to bird songs, or using public cams. Ayer Hitam Utara Forest Reserve is a peat swamp forest, a type of tropical moist forest with a dense layer of acidic peat and serves as a habitat for a diverse range of species. This study aims to identify bird species present in Ayer Hitam Utara Forest Reserve and evaluate the potential of avitourism in Ayer Hitam Utara Forest Reserve. A questionnaire was passed to 51 respondents to collect their opinions on developing Ayer Hitam Utara Forest Reserve as an avitourism site. Point count method and mist-netting were performed to record bird species spotted during the sampling period. The sampling has recorded 33 species in total, where there are 2 Vulnerable, 3 Near-Threatened, and 1 Endangered species, and 20 out of 33 species are totally protected under Wildlife Conservation Act 2010. The respondents have given generally positive feedback and are interested in visiting Ayer Hitam Utara Forest Reserve. Avitourism can potentially benefit Ayer Hitam Utara Forest Reserve in economic, social, and environmental.